The Role of E–Supply Chain Management, E–Service Quality and E–Customer Relationship Management on Customer Satisfaction of Defense Industries - Arsana, I Putu Yogi; Soediantono, Dwi; Siswanto, Siswanto; Radyawanto, Aris Setyo (Universitas Negeri Makassar, 2022)
The purpose of this study was to determine the satisfaction of defense industries consumers, using the variables E - Service Quality, E - Supply Chain Management and E - Customer Relationship Management. The method used is descriptive quantitative research with a sample of 250 defense industries respondents. Data analysis using Structural Equation Modeling (SEM) with data processing tools SmartPLS 3.3.3. The results of the research show that simultaneously E - Service Quality, E - Supply Chain Management, and E - CRM have a significant effect on defense industries consumer satisfaction. It can be said that simultaneously E - Service Quality, E - Supply Chain Management, and E - CRM have a significant effect on customer satisfaction.